Predictors of smokeless tobacco consumption among women: a community based study in a slum of Kolkata - Dasgupta, Aparajita; Pal, Manika; Paul, Bobby; Bandyopadhyay, Lina (International Journal Of Community Medicine And Public Health, 2018)
Background: Tobacco consumption is one of the major preventable causes of death in India. Use of smokeless tobacco (SLT) is associated with oral and other cancers, adverse reproductive outcome and cardiovascular diseases. Prevalence of SLT consumption varies widely in different countries including India affecting people of different sex and age groups with varied socioeconomic, cultural and educational background. Methods: A community based, observational, cross-sectional study was conducted in a slum of Kolkata with the aim of determining the prevalence of SLT use and its predictors among women aged 15 years and above, by simple random sampling 159 study participants were selected. Interviews of the participants were conducted using structured questionnaire. Data were summarised and adjusted with descriptive statistics and binary logistic regression analysis in SPSS (version 16). Results: The prevalence of current SLT use was found to be 36.5%. On multivariable logistic regression, it was observed that there was significant association between SLT use and increasing age AOR (CI) 2.578 (1.131-5.876), lower SE status AOR (CI) 2.332 (1.076-5.054), lower educational level AOR (CI) 2.76 (1.163-6.295) and poor knowledge about SLT. AOR (CI) 2.191 (1.066-4.503). Quit attempt in last one year was 18.9% while missed opportunity for counselling by health care providers was 79%. Conclusions: Emphasis on IEC activities and stringent legislation in addition to the existing strategies of the national program are recommended. All efforts should be made to bring the women from behind the curtain and educate them about hazards of SLT consumption.